Discordances between molecular assays for rifampicin resistance in Mycobacterium tuberculosis: frequency, mechanisms and clinical impact. (4th February 2020) - Van Rie, Annelies; Whitfield, Michael G; De Vos, Elise; Scott, Lesley; Da Silva, Pedro; Hayes, Cindy; Heupink, Tim H; Sirgel, Frederick A; Stevens, Wendy; Warren, Robin M
Abstract: Background: Molecular assays are endorsed for detection and confirmation of rifampicin-resistant TB. The frequency, causal mechanisms and impact of discordant results between molecular tests are not well understood. Methods: The prevalence of discordant results was determined by pairwise comparison of molecular test results in a cohort of 749 rifampicin-resistant TB patients in three South African provinces. Culture isolates were sent to a research laboratory for WGS and rifampicin MIC determination. Clinical information was collected through medical file review. Results: The prevalence of discordances between Xpert MTB/RIF and MTBDR plus was 14.5% (95% CI 10.9%–18.9%), 5.6% (95% CI 2.2%–13.4%) between two consecutive Xpert assays and 4.2% (95% CI 2.2%–7.8%) between two consecutive MTBDR plus assays. Likely mechanisms of discordances were false rifampicin susceptibility on MTBDR plus (due to variants not included in mutant probes or heteroresistance with loss of minor variants in culture), false resistance on molecular assay in rifampicin-susceptible isolates, and human error. The healthcare worker changed the treatment regimen in 33% of patients with discordant results and requested 232 additional molecular tests after a first confirmatory test was performed in 460 patients. A follow-up Xpert assay would give the healthcare worker the 'true' rifampicin-resistant TB diagnosis in at least 73% of discordant cases. Conclusions: The high rate of discordant results between Xpert and MTBDR plus has important implications for the laboratory, clinician and patient. While root causes for discordant result are multiple, a follow-up Xpert assay could guide healthcare workers to the correct treatment in most patients.